Treatment and Prognosis of Anaplastic Thyroid Carcinoma: A Clinical Study of 50 Cases. - Tian-Run Liu; Zhi-Wen Xiao; Hai-Neng Xu; Zhen Long; Fan-Qin Wei; Shi-Min Zhuang; Xiao-Mei Sun; Liang-En Xie; Jia-Sheng Mu; An-Kui Yang; Guan-Ping Zhang; Yi Fan (PLoS ONE, 2016)
Although anaplastic thyroid carcinoma (ATC) is rare, it is one of the most aggressive human cancers. The optimal multimodal therapy policy of ATC is still debated, and a standardized treatment strategy remains to be established. This study aimed to evaluate the management aspect and prognosis of ATC.The data were analyzed retrospectively for 50 patients with ATC to evaluate the clinical characters, management and factors influencing survival. Survival analysis was performed by Kaplan-Merier method and log-rank test, and multivariate analysis was performed using Cox proportional hazard model.The 1-year and 2-year overall survival rates (OS) were 48.0% and 26.0% respectively in all patients, with the 2-year OS of 40.0% and 31.0% and 6.3% for stage IVA, IVB and IVC respectively (P <0.05). In stage IVA and IVB patients, combined surgery with radiotherapy improved overall survival, and the 2-year OS were 50.0% and 35.7% respectively in the group with combined surgery with radiotherapy and the group with surgery with only (P <0.05). Postoperative radiotherapy improved local control rate in stage IVA and IVB patients (P <0.05). However, surgery, radiotherapy or chemotherapy could not improve the survival of stage IVC patients. Multivariate analysis showed that distant metastases, surgery, radiotherapy and tumor residue could predict the prognosis.Combined surgery and radiotherapy could improve overall survival in stage IVA and IVB patients. Patients with ATC have a bad prognosis. Distant metastases, surgery, radiotherapy and tumor residue are the most important factors affecting the prognosis.